Peran Keluarga Dalam Pola Asuh Pada Balita Stunting Di Keluharan Kutowinangun Lor Kota Salatiga - Mariana Octaviany Leonora Pah; Alvianto Wahyudi Utomo; Daru Purnomo (Jurnal Interaksi Sosiologi, 2024)
Stunting is a form of growth process that is hampered by nutritional problems. One of the factors causing stunting is parenting style. Parenting style is the family's ability to provide support and attention to fulfill the needs of toddlers in their growth and development. The aim of the research is to analyze the role of the family in parenting patterns of stunted toddlers in Kutowinangun Lor Village. This research uses a qualitative descriptive method, the approach is used to analyze the role of the family in the parenting style given to stunted toddlers, and the informants are the families of stunted toddlers. Data was collected through observation, interviews, documentation, and data was processed according to qualitative analysis from the results of interviews conducted with families of toddlers. The research results show that in Kutowinangun Lor Village, in 2024 there will be 8 toddlers affected by stunting, where the toddlers are cared for by parents or other family members. In providing parenting patterns for toddlers, it is not only the role of the family but also the role of other actors to assist in providing appropriate parenting patterns for toddlers, such as the role of health authorities, namely health centers and posyandu in providing health check services for growth and development for toddlers, as well as The role of the government, namely sub-districts, provides assistance in providing food or other assistance for families of stunted toddlers. However, with a lack of knowledge about good and correct parenting patterns, toddlers are easily affected by stunting. So it can be concluded that the role of family and other actors is very much needed in providing good and correct parenting patterns for stunted toddlers.